Negotiating Cultural Authenticity: Translation Techniques of Addressee Terms in Asmarandana Verses of Babad Banyumas - Yulianita, Nadia Gitya; Hadiati, Chusni (Journal of Language and Literature Studies, 2026)
This study aims to analyze how addressee terms are translated in the Serat Babad Banyumas Mertadiredjan, an important historical text made up of 617 traditional Javanese poems called macapat or verses. Translation plays an important role in keeping local knowledge alive, but the strict rules of macapat, especially its strict patterns of rhythm and syllables (guru wilangan), often require major changes in the language used. This also applies in translating addressee terms, which refer to positions and relationships of Javanese people. In Javanese, addressee terms reflect the hierarchy, power, and intimacy, which do not always have the equivalence in Indonesian. This study employs a qualitative descriptive framework based on the theories of Rifai & Prasetyaningrum (2016) and Molina & Albir (2002), analyzing the tension between poetic brevity and historical referentiality. The data of this study include 107 addressee terms in Asmarandana verses, since it is the most frequently appeared verses in the book. The study shows that there are five different types of terms used to address someone: respect, name, intimacy, kinship, and a new type found in this research called “origin”, and “respect” is the most frequently appeared type. Meanwhile, the most frequently appeared translation technique is established equivalent, then followed by particularization, reduction, borrowing, amplification, and generalization. The analysis shows that the translator works as a cultural bridge, mainly using established equivalence to keep the feudal class system of the Javanese royal court, and particularization to bring back the place names that were lost because of the poetic structure in the original text. One important thing is that the new "origin" category shows that in Javanese history writing, having a rightful place or land is a key part of who people see themselves as. The translation keeps the cultural truth of the Banyumas people by balancing creative expression with clear historical facts. This study offers an alternative to look at the history of ethnic groups and recommends that future research should examine how names are addressed along with digital language studies.